Critical role for arginase II in osteoarthritis pathogenesis. Issue 3 (4th January 2019) - Choi, Wan-Su; Yang, Jeong-In; Kim, Wihak; Kim, Hyo-Eun; Kim, Seul-Ki; Won, Yoonkyung; Son, Young-Ok; Chun, Churl-Hong; Chun, Jang-Soo
Abstract : Objective: Osteoarthritis (OA) appears to be associated with various metabolic disorders, but the potential contribution of amino acid metabolism to OA pathogenesis has not been clearly elucidated. Here, we explored whether alterations in the amino acid metabolism of chondrocytes could regulate OA pathogenesis. Methods: Expression profiles of amino acid metabolism-regulating genes in primary-culture passage 0 mouse chondrocytes were examined by microarray analysis, and selected genes were further characterised in mouse OA chondrocytes and OA cartilage of human and mouse models. Experimental OA in mice was induced by destabilisation of the medial meniscus (DMM) or intra-articular (IA) injection of adenoviruses expressing catabolic regulators. The functional consequences of arginase II (Arg-II) were examined in Arg2 −/− mice and those subjected to IA injection of an adenovirus encoding Arg-II (Ad-Arg-II). Results: The gene encoding Arg-II, an arginine-metabolising enzyme, was specifically upregulated in chondrocytes under various pathological conditions and in OA cartilage from human patients with OA and various mouse models. Adenovirus-mediated overexpression of Arg-II in mouse joint tissues caused OA pathogenesis, whereas genetic ablation of Arg2 in mice ( Arg2 −/− ) abolished all manifestations of DMM-induced OA. Mechanistically, Arg-II appears to cause OA cartilage destruction at least partly by upregulating the expression of matrix-degrading enzymes (matrix metalloproteinase 3 [MMP3] and MMP13) in chondrocytes via the nuclear factor (NF)-κB pathway. Conclusions: Our results indicate that Arg-II is a crucial regulator of OA pathogenesis in mice. Although chondrocytes of human and mouse do not identically, but similarly, respond to Arg-II, our results suggest that Arg-II could be a therapeutic target of OA pathogenesis.